Inhibition of AdeB, AceI, and AmvA Efflux Pumps Restores Chlorhexidine and Benzalkonium Susceptibility in Acinetobacter baumannii ATCC 19606 - Migliaccio, Antonella; Esposito, Eliana Pia; Bagattini, Maria; Berisio, Rita; Triassi, Maria; De Gregorio, Eliana; Zarrilli, Raffaele (Frontiers in Microbiology, 2022)
The management of infections caused by Acinetobacter baumannii is hindered by its intrinsic tolerance to a wide variety of biocides. The aim of the study was to analyze the role of different A. baumannii efflux pumps (EPs) in tolerance to chlorhexidine (CHX) and benzalkonium (BZK) and identify non-toxic compounds, which can restore susceptibility to CHX and BZK in A. baumannii. A. baumannii ATCC 19606 strain was tolerant to both CHX and BZK with MIC and MBC value of 32 mg/L. CHX subMIC concentrations increased the expression of adeB and adeJ (RND superfamily), aceI (PACE family) and amvA (MFS superfamily) EP genes. The values of CHX MIC and MBC decreased by 8-fold in adeB and 2-fold in amvAor aceI mutants, respectively, while not affected in adeJ mutant; EPs double and triple deletion mutants showed an additive effect on CHX MIC. CHX susceptibility was restored in double and triple deletion mutants with inactivation of adeB gene. BZK MIC was decreased by 4-fold in adeB mutant, and 2-fold in amvA and aceI mutants, respectively; EPs double and triple deletion mutants showed an additive effect on BZK MIC. BZK susceptibility was recovered in adeB aceI adeJ and ∆amvA ∆adeB ∆adeJ triple mutants. The structural comparison of AdeB and AdeJ protomers showed a more negatively charged entrance binding site and F-loop in AdeB, which may favor the transport of CHX. The carbonyl cyanide m-chlorophenylhydrazine protonophore (CCCP) EP inhibitor reduced dose-dependently CHX MIC in A. baumannii ATCC 19606 and in adeJ, aceI or amvA mutants, but not in adeB mutant. Either piperine (PIP) or resveratrol (RV) at non-toxic concentrations inhibited CHX MIC in A. baumannii ATCC 19606 parental strain and EPs gene deletion mutants, and CHX-induced EP gene expression. Also, RV inhibited BZK MIC and EP genes expression in A. baumannii ATCC 19606 parental strain and EPs mutants. These results demonstrate that tolerance to CHX and BZK in A. baumannii is mediated by the activation of AdeB, AceI and AmvA EPs, AdeB playing a major role. Importantly, inhibition of EP genes expression by RV restores CHX and BZK susceptibility in A. baumannii.